Cost-effectiveness impact of rivaroxaban versus new and existing prophylaxis for the prevention of venous thromboembolism after total hip or knee replacement surgery in France, Italy and Spain - Monreal, Manuel; Folkerts, Kerstin; Diamantopoulos, Alex; Imberti, Davide; Brosa, Max (Thrombosis and Haemostasis, 2013)
Venous thromboembolism (VTE) has a significant impact on healthcare costs but is largely preventable with anticoagulant prophylaxis using low-molecular-weight heparins (LMWHs), such as enoxaparin or dalteparin. Rivaroxaban and dabigatran etexilate are two new oral anticoagulants (NOACs) both compared with enoxaparin in separate trials. A decision analytic model with a healthcare and national payer perspective over a five-year time horizon was used to evaluate the cost-effectiveness of the NOACs for VTE prophylaxis after total hip replacement (THR) or total knee replacement (TKR) in France, Italy and Spain. Efficacy and safety data were obtained from randomised controlled trials of rivaroxaban vs enoxaparin and an indirect statistical comparison for rivaroxaban vs dabigatran. Rivaroxaban demonstrated dominance across all comparisons, indications and countries. In THR, total per-patient costs were reduced by up to €160 in the enoxaparin comparison and €115 in the dabigatran comparison, respectively. In addition, quality-adjusted life-years (QALYs) were increased by up to 0.0011 and 0.0012 in each comparison, respectively. Similarly, total costs were reduced in TKR by up to €137 and €28 in the enoxaparin and dabigatran comparisons, respectively. The total number of QALYs was increased by up to 0.0014 in the enoxaparin comparison and 0.0005 in the dabigatran comparison. The results were driven by costs since the incremental benefits were minimal. Rivaroxaban use could result in substantial healthcare cost savings and improved quality of life. The results are applicable across three European countries with differing healthcare systems so, potentially, could be generalised to a much wider population.
Keywords: Cost-effectiveness; quality of life; orthopaedic surgery; rivaroxaban; venous thromboembolism